Efektivitas Mediasi sebagai Alternative Dispute Resolution Terhadap Perkara Perceraian di Pengadilan Agama Pematangsiantar - Rayani Saragih; Maria Ferba Editya Simanjuntak (Mahesa Research Center, 2020)
This study aims to analyze the effectiveness of meditation on divorce cases in the Pematangsiantar Religious Court. The problem in this research is focused on how to implement Mediation in divorce cases at the Pematangsintar Religious Court. The research method in this research is empirical normative legal research, namely by analyzing the related regulations by summarizing them with the results of data obtained directly from the Pematangsianta Religious Court, then the data is analyzed qualitatively. This study concludes that mediation as an Alternative Dispute Resolution (ADR) is seen as an effective and fair way of dispute resolution. Mediation outside the court is regulated in Article 6 of Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Mediation as a decision-making mechanism or a peace agreement is the main authority of the disputing parties and maintains good relations. Mediation must be carried out first in divorce cases before the judge decides in the divorce case, because every judge's decision that does not go through mediation is considered. null and void. The Mediator Judge as much as possible carries out a mediation process with the parties in the case so that the marriage is maintained. However, the success of mediation lies in the good faith of both parties in following and compliance with the mediation process.